Development of teaching factory competency-based for vocational secondary education in Central Java, Indonesia - Sintha Wahjusaputri; Bunyamin Bunyamin (Institute of Advanced Engineering and Science, 2022)
This research was conducted to analyze the teaching factory model in vocational high school (sekolah menengah kejuruan/SMK) in Central Java Province, Indonesia according to the teaching factory's success factors. This research used meta-ethnography for qualitative methods and Delphi technique, Research and Development, and social problem-solving models for quantitative methods. This research involved five vocational secondary education in Central Java Province, with 140 students as the respondents. The findings of teaching factory model implementation are applied to school management, human resources, marketing promotion, workshops, laboratories, learning patterns, and business and industry relationships. This model should increase the competency of graduates relevant to business and industry needs in the 4.0 era industry.